The Effect of Artificial Intelligence, Automation, and Burnout on the Performance of Generation Z Employees in the City of Samarinda - Nurhayati, Nurhayati; Dewi, Catur Kumala; Sunarto, Sunarto (Journal Research of Social Science, Economics, and Management, 2026)
This research examines the influence of Artificial Intelligence (AI), automation, and burnout on the performance of Generation Z employees in Samarinda City. The rapid development of digital technology has prompted companies to adopt AI and automation to improve efficiency, while simultaneously increasing the risk of burnout among young workers who are highly adaptive to technological change. Using a quantitative approach, data were collected from 96 Gen Z employees through an online questionnaire employing a Likert scale. The samples were selected using purposive sampling, and the data were analyzed with multiple linear regression using SPSS. The findings show that AI has a positive but insignificant effect on employee performance due to its suboptimal utilization and the fact that not all job positions have integrated AI-based systems. Automation has a positive and significant effect, indicating that automated processes enhance efficiency, accelerate task completion, and reduce human error. Conversely, burnout has a negative and significant effect on performance, suggesting that high levels of stress, emotional fatigue, and workload pressure lead to decreased productivity. Overall, AI, automation, and burnout simultaneously have a significant influence on Gen Z employee performance, emphasizing the importance of integrating technological advancement with effective stress management strategies to maintain optimal performance in the digital era.